Mechanism study on the soil mechanical behavior of the mixed soil based on energy multi-scale method - Chen, Jian; Yuan, Jie; Tong, Huawei; Fang, Yingguang; Gu, Renguo (Frontiers in Materials, 2023)
The presence of mixed soil is widespread in nature, rendering it susceptible to geological hazards such as landslides, liquefaction, and debris flows. This soil type displays pronounced structural anisotropy due to its diverse mineral composition and the broad range of particle sizes it encompasses across multiple geometric scales. However, there exists an array of conflicting research outcomes concerning the impact of particle composition, size, and content on the mechanical properties of mixed soil. This study delves into the mechanical behavior of mixed soil across varying particle contents and sizes using direct shear testing. Subsequently, the distinctive mechanical responses are dissected by scrutinizing the interplay of particle contact interfaces.Concurrently, the underlying mechanism behind this behavior is explored by examining particle surface adsorption energy through a multi-energy scale approach. In conclusion, the following findings are established:(1) The influence of fine particle content (FC) on mixed soil strength varies according to distinct filling conditions; (2) The contribution to mixed soil strength differs among particles with distinct mineral components;(3) Sand particle size within mixed soil holds no sway over its strength under equivalent mass conditions; (4)The particle surface energy equation derived from the multi-energy scale technique comprehensively elucidates the interplay between particle composition, content, and mechanical behavior in mixed soil.